THESIS THEME:YOUTUBE, TIKTOK, AND COUNTRY LEARNING: HOW SOCIAL MEDIA SHAPES NATIONAL UNDERSTANDING AMONG YOUTH - Rasuljon Ibragimov (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In recent years, social media platforms like YouTube and TikTok have transformed how young people learn about their own and other countries. This thesis investigates the role of social media content in shaping youth perceptions of national identity and stereotypes. Through qualitative content analysis of videos, a survey of young users, and discourse analysis of comments, this research highlights the impact of informal digital learning on national understanding. The findings suggest that social media significantly influences youth's views of countries, often mixing entertainment with cultural education. The study offers insights for educators and policymakers on the importance of media literacy in the digital age.